Endoscopic retrograde cholangiopancreatography in Ayrshire, Scotland: a comparison of two age cohorts. Issue 2 (May 2015) - Pericleous, Stephanos; Smith, Laura Isobel; Karim, Muhammad Ali; Middleton, Nicos; Musbahi, Aya; Ali, Abdulmajid
Background and aims: There is an increased trend in prevalence of pancreato-biliary disease in the elderly population. Consequently there is an increasing demand for endoscopic retrograde cholangiopancreatography (ERCP). The aims of this study were to compare ERCP outcomes in patients over 80 with those aged between 60 and 79 years and with the published literature. Methods and results: Data were collected from a prospectively maintained database. All patients over the age of 60 years who underwent ERCP from May 2010 to May 2012 were identified. Two cohorts were formed, group A: 60–79 years ( n = 66) and group B: > 80 years old ( n = 49). Data on indications for ERCP, outcome, complications and repeat procedures were collected. One hundred and fifteen patients between the age of 60 and 92 years were identified. Group A had a total of 89 ERCPs and group B 69. Cannulation, overall procedure success, complication and mortality rates were comparable between both groups. Group B contained two cases of perforation with one associated mortality (1.4%) which did not reach statistical significance. Conclusions: ERCP in octogenarians is safe and effective when compared to patients aged 60–79.